Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Efficiently photocatalytic synthesis of a special dye intermediate with CO2 for preparing a disperse dye SCFM-ANCY suitable for supercritical coloration of bio-based fibers - Yang-Sheng Zhou; An-Tong Liu; Yi-Wei Shi; Lin Xie; Jia-Jie Long (Process Safety and Environmental Protection, 2026)

Transplanting highly active copper sites into stable MOFs for SAW humidity sensor with bio-inspired anti-pollution microhole array - Chengxu Lin; Jiaxin Liu; Xunyu Yuan; Shilong Peng; Shuang Xi; Hu Long; Zhiyong Liu; Guanglan Liao; Tielin Shi (Chemical Engineering Journal, 2026)

A 13,100-year record of net primary productivity from subtropical China reveals shifting climatic and anthropogenic controls - Lin Zhao; Shanshan Meng; Zijian Liu; Tengwen Long; Zhiguo Rao; Haibin Wu (Anthropocene, 2026)

Wheat germ protein in functional foods: structure, processing, applications, and mechanistic insights - Long Pan; Jing-Yang Cai; Ai-Mei Liao; Lin-Lin Ding; Yin-Chen Hou; Ji-Hong Huang; Xin Wang; Ya-Wei Zhao; Na Liu; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A synergistic strategy combining passive insulation and active discharge for mitigating thermal runaway propagation in lithium-ion batteries - Peng Liu; Xingyu Long; Tao Cao; Jiayi Ge; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2026)

Urea-melamine-derived nitrogen-doped biochar flow electrodes for enhanced treatment of nickel-containing electroplating wastewater - Jian Peng; Ziyi Deng; Wei Liu; Hande Zhang; Yangxiong Huang; Ruixiong Huang; Rikun Lai; Yong Yang; Jianyou Long; Wubiao Lin; Jie Shu; Huosheng Li (Journal of Environmental Chemical Engineering, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

A semi-analytical solution for transient dynamic impact responses of airport runway pavements with HWD interpretation - Lin Li; Liu Peng; Zhang-Long Chen; Weibing Gong (Computers and Geotechnics, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

CAMP-negative group B Streptococcus in pregnant women: molecular and clinical features with implications for diagnostics and neonatal management - Lianfen Huang; Zeying Lin; Sufei Zhu; Chengman Fong; Zengyu Tan; Kankan Gao; Manqiu Kang; Zimeng Liu; Xiaolan Chen; Huamin Zhong; Yongqiang Xie; Bingshao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Multidimensional chemoprofiling of hybrid and wild Broussonetia papyrifera : sustainable utilization analysis of wild resource substitutes - Yue Ren; Ziye Cheng; Chunmei Yang; Long Han; Xianjun He; Yuqi Liu; Lin Ma; Chuhan Wang; Ziyi Shan; Wen Qin; Xiaofan Yuan (Natural Product Research, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Multi-time scale energy management and optimization for hybrid power ships considering lifetime balance and extension of multi-stack fuel cell systems - Xiangguo Yang; Xingwei Zhou; Xin Li; Yufan Wang; Fei Long; Telu Tang; Lin Liu; Yifan Liu (Ocean Engineering, 2026)

Vegetation-hydrology coupling in subtropical China during the Younger Dryas: A quantitative reconstruction from high-resolution pollen records at Luoxiao Mountains - Lin Zhao; Jinlong Liang; Zijian Liu; Tengwen Long; John Dodson; Lidan Liu; Yunxia Li; Zhongwei Shen; Zhiguo Rao; Xiaojian Zhang; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Secondary interfacial polymerization seals defects to repurpose water treatment thin film composites membranes for CO2 capture - YiKai Wang; Zixue Zhao; Long Shi; Tianyi Zhou; Haohan Wan; Gang Zhang; Chuanrong Liu; Wenju Jiang; Lin Yang; Lu Yao; Junfeng Zheng; Zhongde Dai; et al. (Chemical Engineering Journal, 2026)

Multifunctional ion-exchange membrane for uniform zinc deposition in highly reversible aqueous zinc-ion batteries - Juan Wu; Shuang Liu; Zilian Zhang; Yi Zheng; Jia-Lin Yang; Xing-Long Wu; Yude Wang (Chemical Engineering Journal, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

The specificity and selectivity of aptamer depends on the binding epitope: insights from aptamer Hislxl-2a - Xiaoli Liu; Xiangru Zhang; Xinhui Zhao; Mingyan Wu; Xinyue Li; Hengyi Lin; Mingxin Zhang; Zhenhao Long; Tao Bing (Analytica Chimica Acta, 2026)

Effects of Boron on the Lipid Metabolism, Estradiol Concentration, Uterine Morphology and ERα Expression in Ovariectomized Rats - Ziyan Li; Qinglan Liu; Lin Wang; Chun Wang; Long Wang; Shenghe Li; Qianqian Hu (Biological Trace Element Research, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

A bipolar membrane-driven proton self-supply strategy for the sustained and efficient electrosynthesis of Na2S2O4 from desulfurization byproduct - Yingxue Fu; Jun Wu; Hao Chen; Lin Wu; Zhujiang Wang; Yelin Zhu; Jiaqi Long; Zhipeng Tang; Fenghua Shen; Kaisong Xiang; Hui Liu (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Tetrahydroberberine targets the bcl-2 promoter G-quadruplex to trigger mitochondrial apoptosis and inhibit nasopharyngeal carcinoma progression - Yiyin Long; Bingyi Xiao; Yanhong Hou; Liduan Huang; Xiangyue Hu; Xinyi Liu; Yuxun Lin; Tianfen Xu; Guosheng Tang; Yuqing Wang; Yi Cai (Chemico-Biological Interactions, 2026)

Predicting Rate of Penetration of Horizontal Wells Based on the Di-GRU Model - Tao Pan; Xianzhi Song; Baodong Ma; Zhaopeng Zhu; Lin Zhu; Muchen Liu; Chengkai Zhang; Tengda Long (Rock Mechanics and Rock Engineering, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

A membrane-mediated algal–bacterial coupling strategy for energy – efficient and low-carbon PHA production - Long Huang; Lin Liu; Guangyi Zhang; Guoqiang Li; Yingke Fang; Yuan Li; Huiying Yang; Hongbin Xu (Bioresource Technology, 2026)

Analysis of urban design rainstorm patterns based on parameter estimation and model approaches - Jun Zhao; Lin Yang; Long Zhu; Cuishan Liu; Zhenxin Bao; Min Liu; Qiyan Huang; Sadashiv Chaturvedi; Yu Liu; Yuhan Zhao (Stochastic Environmental Research and Risk Assessment, 2026)

Challenges and solutions in seismic geomorphology of ultra-deep carbonates: insights from the Cambrian Longwangmiao formation, central Sichuan Basin, China - Lei Tan; Xiao Feng; Gang Zhou; Lin Qiao; Ya Zhang; Hongyu Long; Hong Liu; Minxing Li; Jianbo Huang (International Journal of Earth Sciences, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Influence of calcination temperature on nutrient removal from aquaculture wastewater by composite substrate made of pyrite and biochar - Bolin Huang; Gang Peng; Yan Zhang; Lin Tan; Shiyang Zhang; Siyuan Wu; Qirui Zhang; Long He; Zhaojun Gu; Xingguo Liu (Journal of Environmental Chemical Engineering, 2026)

Preparation of fluorescent wood based on a novel flavonoid skeleton fluorescent probe for naked eye detection of dichloromethane, trichloromethane, and carbon tetrachloride - Xue Mei; Qingmao Long; Aijiao Lu; Feng Wang; Xiaojia Zhu; Yanfei Lin; Xijuan Chai; Lianpeng Zhang; Li Liu; Guanben Du (Journal of Environmental Chemical Engineering, 2026)

Gut microbiota-derived propionate alleviate traumatic painful neuroma through inhibiting the RIG-I-NF-κB–mediated neuroinflammation - Furong Huang; Anhao Guo; Shen Liu; Haotian Liu; Zhe Zhang; Tao Lin; Shanyin Xiao; Kongmei Luo; Junhe Kong; Long Wu; Hede Yan (Food Research International, 2026)

Covalent modification of whey protein isolate by rosmarinic Acid: Impacts on physicochemical and functional properties - Qing Yang; Shiyun Chen; Xuanpei Wang; Yijie Chen; Lin Xu; Xiao Guo; Zhiyong Gong; Hao-Long Zeng; Xin Liu (Food Hydrocolloids, 2026)

Risk classification and zoning management of heavy metal pollution in paddy soils: A model coupling soil health and source apportionment - Ying Luo; Zhe Wang; Jia-qian Zhang; Chao-liang Peng; Kai Ye; Zhen-long Zhang; Wen-xue Lin; Jing-yan Zhang; Yi-ming Chen; Wei-hao Wang; Jia-xin Liu; Duan Tian; et al. (Environmental Research, 2026)

Tailoring pH-switchable self-dispersible N-halamine microspheres as multifunctional additives for lyocell fibers - Jie Zhao; Lian-Yi Qu; Jiang-Long Liu; Lin Zhang; Zhi-Ming Jiang; Yun Liu; Ying-Jun Xu (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

Geothermal hydrogeochemical conditions and genesis of the Mianhuakeng uranium deposit, South China - Siqi Wang; Xiting Long; Jianjun Hu; Feng Liu; Jingyu Lin (Geothermics, 2026)

Immunological Characteristics of Triploid Grass Carp (Ctenopharyngodon idella) and evaluation of its phagocytosis in the macrophages of head kidney - Xiaoman Huang; Zixuan E; Hao Yang; Guihong Lai; Shuang Liu; Shujia Liao; Jiaqi Lin; Siyi Liu; Chen Long; Haoran Lin; Danqi Lu; Shuisheng Li; et al. (Fish & Shellfish Immunology, 2026)

Promotion of nitric oxide to ammonia via nickel species enhanced active hydrogen generation - Hui Liu; Lin Wu; Yingxue Fu; Zhujiang Wang; Jiaqi Long; Jing Yuan; Xinlei Wang; Jieyu Li; Jun Wu; Kaisong Xiang (Chemical Engineering Journal, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Multi-objective optimization of a semi-submersible floating wind Platform: Integrating cost, stability, and strength - Siqi Lai; Hongwei Liu; Yajing Gu; Rongfu Li; Long Fang; Yonggang Lin; Souleymane Drabo; Xiangheng Feng (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Metabolite composition and taste quality of Eriocheir sinensis under different steaming methods - Renyue Zhang; Fengyi Qiao; Yuyao Shi; Zehui Qiu; Liu Lin; Xichang Wang; Long Zhang (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Biocontrol potential and cryopreservation of marine ciliates for sustainable management of bacterial pathogens in aquaculture - Xin-Long Liu; Sin-Wei Lin; Wei-Yu Yeh; Hung-Yun Lin; Han-Jia Lin (Fish & Shellfish Immunology, 2025)

A cellulose-based near-infrared fluorescent probe for ratiometric imaging and visual monitoring of ClO− in water via smartphone - Wei Bi; Chuanli Ren; Yuxin Xiao; Feng Wang; Qingmao Long; Yanfei Lin; Xinjie Yang; Li Liu; Lianpeng Zhang; Guanben Du (Environmental Research, 2025)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

Dynamic structural reconstruction of CuO under reaction conditions enhances photocatalytic activity in C H bond functionalization - Shaohui Zhang; Jia Liu; Yan Pu; Yifang Zhang; Yingcong Wei; Huaxiang Lin; Jinlin Long; Rongjian Sa; Xianzhi Fu; Rusheng Yuan (Chemical Engineering Journal, 2025)

Photoactivation assisted efficient triplet exciton filling for daylight-visible ultra-bright long lived room temperature phosphorescence - Zhaorun Tang; Lin Ding; Jiyang Long; Zhihao Guan; Xianwen Ke; Ruyi Wei; Xinghai Liu (Chemical Engineering Journal, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Construction of a prognostic risk model for clear cell renal cell carcinomas based on centrosome amplification-related genes - Bingru Zhou; Fengye Liu; Ying Wan; Lin Luo; Zhenzhong Ye; Jinwei He; Long Tang; Wenzhe Ma; Rongyang Dai (Molecular Genetics and Genomics, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Experimental investigation and mechanism analysis of mitigating thermal runaway propagation in lithium-ion battery modules by high-rate discharge - Peng Liu; Xingyu Long; Kuijie Li; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

PolInSAR forest height inversion considering parameter correlation and vertical polarization scattering differences - Yongsheng Liu; Dongfang Lin; Sichun Long; Xuan Wang; Kailin Zhu (Advances in Space Research, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Pressure gradient enhanced air sparging for removal of high-concentration methyl tert-butyl ether in low-permeability soils - Lin Qin; Xu Long; Jingjing Liu; Fusheng Zha; Qiong Wang; Qiao Wang; Su Wei; Mengyu Zhang (Journal of Environmental Chemical Engineering, 2025)

A new exhalative sedimentary metallogenetic model for Permian manganese deposits in China - Zhichen Liu; Yu Liu; Sui Zhang; Lin Xiao; Jianxi Long; Deng Chen; Yang Wang; Zequan Wei; Yi Zheng; Liang Xiao (Journal of Asian Earth Sciences, 2025)

Enhanced heat transfer and flow dynamics in liquid helium-free MRI cooling devices: A physical-based modeling approach - Changhao Luo; Zhiqiang Long; Yi Deng; Guanhua Liu; Meng Lin (International Journal of Refrigeration, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Evaluation of the inhibitory effects of carbamate pesticides on human carboxylesterases - Chen-yuan Liao; Xiao-lei Yi; Yu-xin Yang; Jia-min Gong; Yu-Lin Ma; Fei Long; Zhen-zhong Liu; Zuo Du (Toxicology and Applied Pharmacology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Thermal processing of Oilseeds: Multidimensional impacts on Maillard reaction chemistry, nutritional safety, and technological innovations in quality control - Xinyu Li; Xinyue Liu; Zhiqiang Kong; Lin Li; Long Li; Marie-Laure Fauconnier; Minmin Li (Trends in Food Science & Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Two new ursane type triterpenoids from adult leaves of Cyclocarya paliurus - Shan-Xuan Zhang; Meng-Fei Liu; Yu-Ling Tan; Jin-Long Duan; Qiao-Lin Xu; Jian-Wen Tan (Phytochemistry Letters, 2025)

Juvenile macular degeneration in nonhuman primates generated by germline knockout of ABCA4 gene - Ya Ma; Qiang Lin; Hai-Long He; Yi-Xin Liu; Min Li; Xiao-Hui Zhang; Zi-Bing Jin (Science Bulletin, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Demulsification characteristics of electrostatic–swirling coupling enhanced migration - Guidong Chen; Silong Feng; Shuo Liu; Lin Li; Xiangyi Long; Qiang Yang; Hao Lu (Journal of Water Process Engineering, 2025)

Milk peptides alleviate irritable bowel syndrome by suppressing colonic mast cell activation and prostaglandin E2 production in mice - Yu Zhang; Zhiqing Lin; Qi Yao; Jian He; Haotian Feng; Wenyi Zhang; Zhigang Liu; Tian Yuan; Xuebo Liu; Long Ding (Food Research International, 2025)

Field tests and structural performance evaluation of existing reinforced concrete hollow slab beam bridges - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Mass transfer analysis of a concentration-regulated metal-assisted chemical etching system and its application in Si nanohole fabrication - Jiecai Long; Xuan Zhang; Haojun Zhang; Haoya Wang; Congkai Xie; Xun Chen; Guohuai Lin; Yun Chen; Xin Chen; Huitao Liu; Renquan Lu (Chemical Engineering Journal, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Astaxanthin complexes of five plant protein fibrils: Aggregation behavior, interaction, and delivery properties - Fengqiujie Wang; Liu Lin; Xichang Wang; Long Zhang; Ningping Tao (Food Hydrocolloids, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Pepper feeding derivative Brucella sp. in the gut of Spodoptera litura (Lepidoptera: Noctuidae) affect the growth and development of host larvae - Yu Wang; Zhou Yu; Bei-Long Chen; Shao-Shao He; Zi-Yao Liu; Zheng Zhai; Lin Chen; Jiang-Bin Fan; Huan Yu; Zhi-Ping Zuo; Yong-Sheng Zhang (Pesticide Biochemistry and Physiology, 2025)

Growth history of garnet from the Dulong Sn-Zn-In polymetallic deposit: Geochemical and U Pb age constraints and their metallogenic significance - Shiyu Liu; Lin Ye; Yuping Liu; Hansheng Long; Chen Wei; Zhenzhong Xiang (Journal of Geochemical Exploration, 2025)

Promotion effect of Ce and Ta co-doping on the NH3-SCR performance over V2O5/TiO2 catalyst - Long Liu; Xin Shen; Zhihua Lian; Chunxi Lin; Ying Zhu; Wenpo Shan; Hong He (Journal of Environmental Sciences, 2025)

Co-delivery of astaxanthin using positive synergistic effect from biomaterials: From structural design to functional regulation - Fengqiujie Wang; Jianhua Zeng; Liu Lin; Xichang Wang; Long Zhang; Ningping Tao (Food Chemistry, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

Waterproofing enhancement mechanism of the double sealing gaskets: Experimental test and theoretical analysis - Hua-Yong Li; Huai-Na Wu; Dong-Lin Feng; Lei Liu; Qing-long Cui; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Adrenomedullin gene delivery rescues estrogen production in Leydig cells via the inhibition of TGF-β1/Smads signaling pathway - You-wen Luo; Xia-lian Zhu; Zhi-min Yang; Jian-hua Zhou; Tong Tao; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Recent advances in iron-based catalyst-driven persulfate activation for organic pollutant degradation - Huawen Hu; Jin Liu; Xiyu Zheng; Kai Zhao; Yinlei Lin; Xuejun Xu; Hangyu Long; Yuyuan Zhang; Xiaowen Wang; Dongchu Chen; Qianjun Deng (Journal of Water Process Engineering, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

Performance evaluation of existing reinforced concrete hollow-slab beams: Experiments and fibre beam element-based model updating - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

Degradation of ofloxacin by activation of persulfate with metal-N co-doped modified peanut shell biochar: The key role of cobalt doping - Wei Qian; Yi-Li Deng; Xiao-Long Liu; Hui Liu; Mao-You Ye; Ying-Ying Li; Yong-Zheng Zhang; Zeng-Hui Diao; Jia-Lin Liang (Journal of Water Process Engineering, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Unintentional emissions of polychlorinated naphthalenes in China: Sources, composition, and historical trends - Ye Huang; Lin Huang; Ying Li; Nazupar Sidikjan; Yunshan Zhang; Yan Chen; Yangmin Chen; Ye Li; Wei Du; Long Chen; Yan Wu; Shanshan Zhang; et al. (Journal of Environmental Sciences, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Evaluation of edible quality and processing suitability of segmented products from silver carp under different thermal processing methods - Xinlei Yu; Jingjing Wu; Zehui Qiu; Yuyao Shi; Liu Lin; Xichang Wang; Long Zhang (Food Research International, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

The effects of dietary supplementation with Enteromorpha prolifera polysaccharide on the growth, immunity, and antioxidant capacity of spotted sea bass Lateolabrax maculatus - Zhongying Long; Longhui Liu; Huihui Qin; Sishun Zhou; Lumin Kong; Jianrong Ma; Hao Lin; Zhangfan Huang; Yi Lin; Zhongbao Li (Aquaculture International, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Comprehensive analysis of epigenetic modifications in alfalfa under cadmium stress - Lin Chen; Xianyang Li; Hao Liu; Fei He; Mingna Li; Ruicai Long; Xue Wang; Junmei Kang; Qingchuan Yang (Journal of Hazardous Materials, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Effects of rosmarinic acid covalent conjugation on the allergenicity and functional properties of egg white protein - Xuanpei Wang; Hao-Long Zeng; Jieli Shang; Yijie Chen; Lin Xu; Jine Wu; Zhiyong Gong; Xin Liu; Qing Yang (Food Hydrocolloids, 2025)

Judicious inhibition of interfacial non-radiative recombination via chlorine-isomerized self-assembled molecules for efficient and durable organic solar cells - Hao Xu; Xingting Liu; Shanlei Xu; Kin-Long Wong; Xinjie Zhou; Huilong Chen; Yijin Lin; Renyong Geng; Weiguo Zhu; Jun Yin; Xin Song (Chemical Engineering Journal, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Submerge-emerge alternation promotes sediment per- and polyfluoroalkyl substance (PFAS) release and bioaccumulation - Ye-bing Shi; Zu-lin Hua; Xiao-qing Li; Song-he Zhang; Jian-long Liu (Science of The Total Environment, 2024)

Unveiling the formation and influence mechanisms of PCDD/F memory effect in wet scrubbers: Fundamental research and field verification - Ying Peng; Yunfeng Ma; Xiaoqing Lin; Jisheng Long; Li Bai; Hailiang Du; Yang Cao; Jiajun Wang; Lu Liu; Xiaodong Li (Science of The Total Environment, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Hesperidin and 5, 7-dimethoxycoumarin act as markers in the chemotaxonomy of Citrus medica L. var. sarcodactylis Swingle and Citrus medica L. - Di Wu; Miao-Miao Zhang; Hong-Ping Long; Xiao-Yuan Lin; Kai Liu (Biochemical Systematics and Ecology, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Vision-based trajectory generation and tracking algorithm for maneuvering of a paddy field robot - Dengbin Fu; Zhiying Chen; Zhiqiang Yao; Zhanpeng Liang; Yinghu Cai; Chuang Liu; Zhenyu Tang; Caixia Lin; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Recombinant avian-derived antiviral proteins cIFITM1, cIFITM3, and cViperin as effective adjuvants in inactivated H9N2 subtype avian influenza vaccines - Shihong Yan; Yikai Chen; Jin Lin; Huimin Chen; Chenqi Hu; Hongyang Liu; Hongxiu Diao; Shasha Liu; Ji-Long Chen (Veterinary Microbiology, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Chronic dietary exposure to glyphosate-induced connexin 43 autophagic degradation contributes to blood-testis barrier disruption in roosters - Qing Liang; Bao-You Liu; Tian-Lin Zhang; Hai-Jing Zhang; Yu-Long Ren; Hai-Peng Wang; Hao Wang; Lin Wang (Science of The Total Environment, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

Removal of antibiotics from aquaculture wastewater using a continuous flow/EC/PMS coupled system - Lulu Long; Jingrong Li; Ting Hou; Min Liu; Yuhuan Lin; Xingwei Zhu; Chao Chen; Gang Yang; Jingsong He (Chemical Engineering Journal, 2024)

Microtopography and hydrological regulation alter CO2 and CH4 fluxes in urban wetlands: Evidence from the Pearl River Delta, China - Kangting Ouyang; Zhihui Wang; Zhongyu Sun; Guangqing Huang; Long Yang; Meijie Liu; Cunxiang Fan; Zhibin Lin (CATENA, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

A novel “on-off-on” electrochemiluminescence aptasensor based on resonance energy transfer as signal amplification strategy for ultrasensitive detection of sulfadiazine in different samples - Youqi Long; Junjie Liu; Yijie Wu; Lin Fu; Lijuan Bai (Food Chemistry, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Mapping and analyzing the spatiotemporal dynamics of forest aboveground biomass in the ChangZhuTan urban agglomeration using a time series of Landsat images and meteorological data from 2010 to 2020 - Zhaohua Liu; Jiangping Long; Hui Lin; Hua Sun; Zilin Ye; Tingchen Zhang; Peisong Yang; Yimin Ma (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Polystyrene nanoplastics induce cardiotoxicity by upregulating HIPK2 and activating the P53 and TGF-β1/Smad3 pathways - Jian-Zheng Yang; Kai-Kai Zhang; Clare Hsu; Lin Miao; Li-Jian Chen; Jia-Li Liu; Jia-Hao Li; Xiu-Wen Li; Jia-Hao Zeng; Long Chen; Ji-Hui Li; Xiao-Li Xie; et al. (Journal of Hazardous Materials, 2024)

Heterogeneous activation of self-generated H2O2 by Pd@UiO-66(Zr) for trimethoprim degradation: Efficiency and mechanism - Yijun Chen; Meina Cheng; Long Jin; Hailiang Yang; Sanjian Ma; Zixia Lin; Guoliang Dai; Xin Liu (Journal of Environmental Management, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Analyzing the influence of Clostridium butyricum on liver health in spotted sea bass (Lateolabrax maculatus) via transcriptomics and metabolomics - Lumin Kong; Jianrong Ma; Hao Lin; Sishun Zhou; Zhongying Long; Huihui Qin; Yi Lin; Longhui Liu; Zhangfan Huang; Zhongbao Li (Aquaculture International, 2024)

Effects of chlorogenic acid supplementation in high-fat diet on antioxidant capacity, immunity, and intestinal health of spotted sea bass (Lateolabrax maculatus) - Jianrong Ma; Lumin Kong; Hao Lin; Sishun Zhou; Yi Lin; Huihui Qin; Zhongying Long; Longhui Liu; Zhangfan Huang; Zhongbao Li (Aquaculture International, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Hydrogen-promoted oxygen reduction Fenton reaction system constructed by Pd/UiO-66(Zr) to efficiently degradate trimethoprim - Yijun Chen; Hailiang Yang; Sanjian Ma; Meina Cheng; Zixia Lin; Long Jin; Xin Liu (Journal of Water Process Engineering, 2024)

Development and characterization of a bacterial enzyme cascade reaction system for efficient and stable PET degradation - Chengyong Wang; Rui Long; Xiran Lin; Wei Liu; Liying Zhu; Ling Jiang (Journal of Hazardous Materials, 2024)

Evaluation of quercetin in alleviating the negative effects of high soybean meal diet on spotted sea bass Lateolabrax maculatus - Longhui Liu; Yanbo Zhao; Zhangfan Huang; Zhongying Long; Huihui Qin; Hao Lin; Sishun Zhou; Lumin Kong; Jianrong Ma; Yi Lin; Zhongbao Li (Fish & Shellfish Immunology, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Construction of short synthetic promoters for optimization of ovalbumin expression level in Saccharomyces cerevisiae - Ying Lin; Xiaomin Dong; Xueqin Lv; Long Liu; Jianghua Li; Guocheng Du; Jian Chen; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2024)

Home-field advantage of litter decomposition differs among leaves, absorptive roots, and transport roots - Xiaoxiang Zhao; Qiuxiang Tian; Anders Michelsen; Qiaoling Lin; Xudong Yuan; Long Chen; Mengzhen Lu; Qinghu Jiang; Rudong Zhao; Feng Liu (Plant and Soil, 2024)

Novel Programmed Death Ligand 1-AKT-engineered Mesenchymal Stem Cells Promote Neuroplasticity to Target Stroke Therapy - Syuan-Ling Lin; Wei Lee; Shih-Ping Liu; Yi-Wen Chang; Long-Bin Jeng; Woei-Cherng Shyu (Molecular Neurobiology, 2024)

Imperceptible liquid metal based tattoo for Human-Machine interface on hairy skin - Weikang Lin; Liqing Ai; Yuanyi Wang; Xiaodan Yang; Junchen Liao; Qiqi Pan; Ying Hong; Shiyuan Liu; Zhihe Long; Bee Luan Khoo; Xi Yao; Zhengbao Yang (Chemical Engineering Journal, 2024)

Self-adaptive and soft-contact ellipsoidal pendulum-structured triboelectric nanogenerator for harvesting water wave energy - Bingqi Zhao; Yong Long; Tianci Huang; Jianan Niu; Yuxiu Liu; Wei Sha; Jiangwen Wang; Zhong Lin Wang; Junyi Zhai; Weiguo Hu (Chemical Engineering Journal, 2024)

Identification of SNPs and candidate genes associate with growth performance in all-female mandarin fish (Siniperca chuatsi) by a genome-wide association study - Dingrui Liu; Jin Zhang; Zhenjiang Zou; Chen Long; Jiaqi Lin; Junyan Zeng; Jingpeng Hou; Linqiang Han; Yanlin Jiang; Shuisheng Li; Yong Zhang (Aquaculture, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Ferrocene-functionalized zirconium-oxo clusters for achieving high-performance thermocatalytic redox reactions - Su-Juan Yao; Jiao-Min Lin; Long-Zhang Dong; Ying-Lin Li; Ning Li; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Dual modification engineering enabled efficient perovskite solar cells with high open-voltage of 1.233 V - Zhongqi Liu; Long Shao; Fancong Zeng; Shuhang Bian; Bin Liu; Yuqi Wang; Yanjie Wu; Yongzhi Shao; Huan Zhang; Yuhong Zhang; Zhicong Shi; Xue Bai; et al. (Chemical Engineering Journal, 2024)

SGIV evades interferon immune response via the degradation of STING-TBK1 complex by VP149 - Xiaolin Gao; Long Lin; Yin Zhao; Yu Wang; Xinmei Yang; Shanxing Liu; Xiaohong Huang; Qiwei Qin; Youhua Huang; Ya Zhang (Aquaculture, 2024)

Ferrate(VI) assists in reducing cytotoxicity and genotoxicity to mammalian cells and organic bromine formation in ozonated wastewater - Ye Du; Tong Liu; Lu-Lin Yang; Zhi-Min Song; Xin Dai; Wen-Long Wang; Bo Lai; Qian-Yuan Wu (Water Research, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Typhoon Chan-Hom (2015) induced sediment cross-shore transport in the mud depo-center of the East China Sea inner shelf - Yunpeng Lin; Yunhai Li; Meng Liu; Liang Wang; Binxin Zheng; Zouxia Long; Jingping Xu (Marine Geology, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

SARS-CoV-2 nucleocapsid protein promotes TMAO-induced NLRP3 inflammasome activation by SCAP–SREBP signaling pathway - Mi-Hua Liu; Xiao-Long Lin; Le-Le Xiao (Tissue and Cell, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Efficient wastewater disinfection using a novel microwave discharge electrodeless ultraviolet system with ozone at an ultra-low dose - Jue-Lin Xiang; Jun-Jie Wang; Zhi-Jing Wu; Bao-Jun Xu; Hai-Sheng Du; Ying Chen; Min Liu; Min-Yong Lee; Wen-Long Wang; Ye Du (Journal of Hazardous Materials, 2024)

Fine roots and extramatrical mycelia regulate the composition of soil organic carbon and nitrogen in a subtropical montane forest - Xiaoxiang Zhao; Qiuxiang Tian; Anders Michelsen; Long Chen; Pengyun Yue; Zhiyang Feng; Qiaoling Lin; Rudong Zhao; Feng Liu (Forest Ecology and Management, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Rapid and efficient preparation of cationized lignin for downstream high value-added utilization of biodegradable antimicrobial nanofibrous membranes - Yu-Fei Gao; Cheng-Ye Ma; Qian Sun; Xin-Xu Zhang; Jing Liu; Jia-Long Wen; Rou-Xi Chen; Hsing-Lin Wang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Cellulase with Bacillus velezensis improves physicochemical characteristics, microbiota and metabolites of corn germ meal during two-stage co-fermentation - Long Chen; Yang Guo; Xin Liu; Lin Zheng; Bingdong Wei; Zijian Zhao (World Journal of Microbiology and Biotechnology, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Hydrological characteristics of the Bering Sea in the summer of 2019 - Hongxia Chen; Lina Lin; Long Fan; Bin Kong; Yan He; Zexun Wei; Na Liu; Yida Xu (Marine Environmental Research, 2024)

Bacteria-driven copper redox reaction coupled electron transfer from Cr(VI) to Cr(III): A new and alternate mechanism of Cr(VI) bioreduction - Xiaoye Min; Kejing Zhang; Jianxin Chen; Liyuan Chai; Zhang Lin; Long Zou; Weizao Liu; Chunlian Ding; Yan Shi (Journal of Hazardous Materials, 2024)

Effect of complex municipal solid waste incineration flue gas on the corrosion of various alloys at 550 °C - Xiaobo Liu; Yin Duan; Lin Zheng; Ling Long; Zeinab Khalid; Qunxing Huang; Xuguang Jiang (Fuel, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Population genomics of the muskox' resilience in the near absence of genetic variation - Patrícia Pečnerová; Edana Lord; Genís Garcia‐Erill; Kristian Hanghøj; Malthe Sebro Rasmussen; Jonas Meisner; Xiaodong Liu; Tom van der Valk; Cindy G. Santander; Liam Quinn; Long Lin; Shanlin Liu; et al. (Molecular Ecology, 2024)
Genomic studies of species threatened by extinction are providing crucial information about evolutionary mechanisms and genetic consequences of population declines and bottlenecks. However, to understand how species avoid the extinction vortex, insights can be drawn by studying species that thrive despite past declines. Here, we studied the population genomics of the muskox ( Ovibos moschatus ), an Ice Age relict that was at the brink of extinction for thousands of years at the end of the Pleistocene yet appears to be thriving today. We analysed 108 whole genomes, including present‐day individuals representing the current native range of both muskox subspecies, the white‐faced and the barren‐ground muskox ( O. moschatus wardi and O. moschatus moschatus ) and a ~21,000‐year‐old ancient individual from Siberia. We found that the muskox' demographic history was profoundly shaped by past climate changes and post‐glacial re‐colonizations. In particular, the white‐faced muskox has the lowest genome‐wide heterozygosity recorded in an ungulate. Yet, there is no evidence of inbreeding depression in native muskox populations. We hypothesize that this can be explained by the effect of long‐term gradual population declines that allowed for purging of strongly deleterious mutations. This study provides insights into how species with a history of population bottlenecks, small population sizes and low genetic diversity survive against all odds.

Herbaceous ornamental plants with conspicuous aesthetic traits contribute to plant invasion risk in subtropical urban parks - Siwei Hu; Cheng Jin; Ruiyan Liao; Li Huang; Lihua Zhou; Yuxiao Long; Min Luo; C.Y. Jim; Wenhao Hu; Dunmei Lin; Shengbin Chen; Changjing Liu; et al. (Journal of Environmental Management, 2023)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

An odorant receptor tuned to an attractive plant volatile vanillin in Spodoptera litura - Zhi-Qiang Wei; Ji-Xiang Wang; Jin-Meng Guo; Xiao-Long Liu; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2023)

Adaptive learning-based recoil control for deepwater drilling riser systems - Yun Zhang; Bao-Lin Zhang; Qing-Long Han; Xian-Ming Zhang; Ximei Liu; Bin Zhang (Ocean Engineering, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Thermally activated delayed fluorescence emitters with bulky four-coordinate boron acceptors for high-performance solution-processed OLEDs - Bowen Li; Zhenming Ding; Zhimin Wu; Meihua Liu; Shaofeng Chen; Dongcheng Chen; Zhigao Li; Long Sang; Yu Liu; Lili Lin; Weiguo Zhu; Xiaobo Wan (Chemical Engineering Journal, 2023)

High-level production of cordycepin by the xylose-utilising Cordyceps militaris strain 147 in an optimised medium - Liangkun Long; Zhen Liu; Yizhou Wang; Qunying Lin; Shaojun Ding; Chuanhua Li; Chunying Deng (Bioresource Technology, 2023)

An in-situ grown high-efficiency Zn-terephthalate metal–organic framework/ZnO hybrid interface protection layer to achieve highly reversible dendrite-free Zn anodes - Pingli Wu; Yi Cao; Heng Cao; Yu Liu; Xiaomin Huang; Jialin Zhang; Yang Cao; Yujia Long; Yijun Zhai; Zhuang Wu; Qiaoji Zheng; Dunmin Lin (Chemical Engineering Journal, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Biogeographic distribution patterns of the bacterial and archaeal communities in two seamounts in the Pacific Ocean - Ning-Hua Liu; Jun Ma; Si-Qi Lin; Kui-Dong Xu; Yu-Zhong Zhang; Qi-Long Qin; Xi-Ying Zhang (Frontiers in Marine Science, 2023)
Seamounts are important components of seafloor topography and have a significant influence on the biogeographic distribution of marine microorganisms. However, current studies on the biogeographic distribution patterns of microorganisms in the ocean around seamounts are still inadequate. This study investigated the bacterial and archaeal communities present in the water column at various depths around the Kocebu and M5 seamounts located in the western Pacific Ocean using 16S rRNA gene high-throughput sequencing. The analyses showed that microbial communities had different alpha diversities and species compositions in samples from the same depth, and disruption of vertical stratification of microbes was observed in deep water layers at both seamounts. The stochastic processes dominated the microbial community assembly around two seamounts, for the Kocebu Seamount, drift accounted for 34.99% and 64.85% in the bacterial and archaeal community assembly processes, respectively; while the corresponding values for the M5 Seamount were 14.07% and 58.65%. Despite the low explanatory power of environmental variables for microbial communities, dissolved inorganic nitrogen was the most significant factor influencing the microbial community structure in seawater around seamounts. Overall, our results revealed that the presence of Kocebu and M5 seamounts enhance the vertical mixing of microbial communities in the surrounding seawater, and stochastic processes dominate microbial community assembly. Considering the numerous seamounts in the global ocean, the impacts of seamounts on marine ecosystems and biogeochemical cycles may have been underestimated.

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

Recent advances in cellulosic materials for aqueous zinc-ion batteries: An overview - Long Cheng; Yang Huang; Sha Yin; Ming Chen; Yihong Liu; Yidan Zhang; Farzad Seidi; Zixia Lin; Huining Xiao (Carbohydrate Polymers, 2023)

Growth performance, digestive capacity and intestinal health of juvenile spotted seabass (Lateolabrax maculatus) fed dietary laminarin supplement - Huihui Qin; Zhongying Long; Jianrong Ma; Lumin Kong; Hao Lin; Sishun Zhou; Yi Lin; Zhangfan Huang; Longhui Liu; Zhongbao Li (Frontiers in Marine Science, 2023)
Laminarin has antioxidant and immunomodulatory properties and favorably impacts gut microbial composition, providing a potential solution for the treatment of intestinal diseases in fish. The aim of this study was to investigate the effects of laminarin on the growth and intestinal health of juvenile spotted seabass, Lateolabrax maculatus . A total of 450 juveniles (initial body weight: 7.14 ± 0.10 g) were randomly divided into 6 groups with 3 replicates per group and 25 fish per replicate. Six diets were prepared with laminarin supplementation at doses of 0% (Control), 0.4% (P0.4), 0.8% (P0.8), 1.2% (P1.2), 1.6% (P1.6), and 2% (P2). Each group was fed the corresponding diet for 8 weeks. The results indicated that dietary laminarin supplementation of 0.4-1.6% enhanced the specific growth rate (SGR), weight gain rate (WGR), and feed conversion ratio (FCR) of juvenile spotted seabass, and the difference was significant in the P0.8 group ( P <0.05). Significantly higher intestinal amylase activity was measured in P0.8 compared with the control group. Trypsin activity was significantly increased in P0.4 and P0.8 groups in contrast to the control ( P <0.05). Lipase activity was significantly increased in P0.4, P0.8, P1.6, and P2 groups in contrast to the control ( P <0.05). Total antioxidant capacity was significantly increased in the P0.8, P1.2, and P1.6 groups compared to the control group ( P <0.05). The P0.8 group exhibited significant increases in reduced glutathione, alkaline phosphatase, and lysozyme levels ( P <0.05), whereas the concentrations of diamine oxidase and D-lactate were significantly decreased ( P <0.05). Furthermore, intestinal villus height, villus width, and crypt depth were significantly increased in P0.8 and P2 groups ( P <0.05), and muscular thickness was significantly increased in the P1.2 group ( P <0.05). Intestinal microbial analysis revealed that the alpha diversity of the laminarin supplemented groups was significantly higher than that of the control group. Moreover, the abundance of intestinal beneficial bacteria Lactobacillus and Klebsiella in P0.4 and P0.8 groups was significantly increased ( P <0.05), indicating that laminarin altered the composition of intestinal flora and the abundance of dominant bacteria, with a low dose being more conducive to the formation of beneficial bacteria. In conclusion, dietary laminarin supplementation can improve the growth performance and intestinal function of juvenile spotted seabass. Based on the regression analyses of weight gain rate and specific growth rate, the optimal supplemental level of laminarin was estimated to be 0.97% and 0.98%, respectively.

The Effects of Porphyra yezoensis Polysaccharides on Intestinal Health of Spotted Sea Bass, Lateolabrax maculatus - Hao Lin; Sishun Zhou; Zhangfan Huang; Jianrong Ma; Lumin Kong; Yi Lin; Zhongying Long; Huihui Qin; Longhui Liu; Yanbo Zhao; Zhongbao Li (Fishes, 2023)
Porphyra yezoensis polysaccharides (PPs) have biological activities such as promoting digestion, functioning as antioxidants, and improving intestinal health. The aim of this study was to investigate the effects of PPs on the intestinal health of spotted sea bass (Lateolabrax maculatus). A total of 360 spotted sea bass (10.53 ± 0.02 g) were randomly divided into six groups. Fish in each group were fed with varying PP concentrations (0, 3, 6, 9, 12, 15 g/kg) for 52 days. The results showed that 12 g/kg PPs significantly increased the body weight gain, specific growth rate, and condition factor, while there was no significant change in the feed conversion ratio. A supplementation dosage of 9 g/kg PPs significantly increased intestinal amylase activity, and 12 g/kg PPs supplementation significantly increased intestinal trypsin activity. In addition, compared with the control group, there was no difference in lipase in the experimental groups. When fed 9 g/kg, the intestinal glutathione content was significantly increased, and the malondialdehyde content was significantly decreased; the effect of PPs on the catalase activity was not significant. PPs improved intestinal morphology, specifically by improving the intestinal villus morphology and increasing the intestinal lining surface area. Compared with the control group, PPs increased the abundance of Firmicutes and Bacteroides. At the genus level, Cyanobacteria, Muribaculaceae, and Lachnospiraceae were the main flora in the intestinal tract of spotted sea bass. In addition, PPs increased ACE and Chao1 indices of the intestinal microorganisms, while the Simpson index and Shannon index did not change significantly, indicating that intestinal microbial composition and abundance had increased to a certain extent. The results indicated that different levels of PPs in feed can improve the intestinal physiological and biochemical indexes, intestinal morphology, and microbial composition, and thus improve the intestinal health of spotted sea bass.

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Neuron-Derived Exosomes Promote the Recovery of Spinal Cord Injury by Modulating Nerve Cells in the Cellular Microenvironment of the Lesion Area - Yi Xu; Zheng-huan Zhu; Xu Xu; Hai-tao Sun; Hong-ming Zheng; Jin-long Zhang; Hong-hai Wang; Jia-Wei Fang; Ya-zheng Liu; Lin-ling Huang; Zhi-wen Song; Jin-bo Liu (Molecular Neurobiology, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

A novel noninvasive brain–computer interface by imagining isometric force levels - Li Hualiang; Ye Xupeng; Liu Yuzhong; Xie Tingjun; Tan Wei; Shen Yali; Wang Qiru; Xiong Chaolin; Wang Yu; Lin Weilin; Jinyi Long (Cognitive Neurodynamics, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

MgO-based binders with different formulations for solidifying Pb and Cd in MSWI fly ash: Solidification effect and related mechanisms - Yin Duan; Xiaobo Liu; Lin Zheng; Zeinab Khalid; Ling Long; Xuguang Jiang (Process Safety and Environmental Protection, 2023)

A novel water disinfection method via cuprous ion generation in a copper ferrite/sulfite system and associated mechanism - Lu Qin; Dongqi Wang; Cong Liu; Guodong Chai; Mingliang Fang; Jiake Li; Hui Wang; Zhe Wang; Haiyu Meng; Xing Zheng; Mengbo Huang; Yi Xiao; et al. (Journal of Water Process Engineering, 2023)

Ultraviolet-based synergistic processes for wastewater disinfection: A review - Yi-Xuan Zhang; Jue-Lin Xiang; Jun-Jie Wang; Hai-Sheng Du; Ting-Ting Wang; Zheng-Yang Huo; Wen-Long Wang; Min Liu; Ye Du (Journal of Hazardous Materials, 2023)

Swc4 protects nucleosome-free rDNA, tDNA and telomere loci to inhibit genome instability - Yue Pan; Can Hu; Lin-Jun Hou; Yu-Long Chen; Jiantao Shi; Jia-Cheng Liu; Jin-Qiu Zhou (DNA Repair, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Phenylpropanoids from the Nitraria tangutorum fruit as glycerol phosphate dehydrogenase inhibitors through in vitro, in silico and in vivo studies - Zhi-Xiang Liu; Lin-Lin Yuan; Nan Zhang; Min Zhao; Yue Li; Ming-Yue Zhao; Yu-Meng Wang; Zi-Zhuo Wang; Yang-Yang Zhang; Jin-Long Tian (Food Bioscience, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

The effects of mycorrhizal associations on fine root decomposition in temperate and (sub)tropical forests - Xiaoxiang Zhao; Qiuxiang Tian; Anders Michelsen; Qiaoling Lin; Rudong Zhao; Xudong Yuan; Long Chen; Juan Zuo; Feng Liu (Plant and Soil, 2023)

Effects of mulberry leaf extract on the intestinal health of spotted sea bass (Lateolabrax maculatus) - Sishun Zhou; Zhangfan Huang; Hao Lin; Lumin Kong; Jianrong Ma; Zhongying Long; Huihui Qin; Longhui Liu; Yi Lin; Zhongbao Li (Frontiers in Marine Science, 2023)
Mulberry leaf extract (ELM) has the functions of promoting growth, antioxidant, improving intestinal microbial composition, thus providing a potential solution the occurrence of fish intestinal diseases. Therefore, this experiment was conducted to explore the effects of ELM on intestinal health of spotted sea bass Lateolabrax maculatus . A total of 360 spotted sea bass (9.00 ± 0.02 g) were selected and randomly divided into 6 groups. Fish in each group were given feed with varying ELM concentration (0, 3, 6, 9, 12, 15 g/kg) for 52 days, respectively. Results show, dietary intake of 9 g/kg ELM increased the weight gain, specific growth ratio and feed intake of the spotted sea bass ( P <0.05). Meanwhile, dietary intake of 9 g/kg ELM increased the activity of enteric trypsin, amylase and lipase ( P <0.05). The enteric catalase activity was improved in fish fed with 3 g/kg ELM ( P <0.05), while a limited effect of ELM on the activity of enteric superoxide dismutase, glutathione, and content of malonaldehyde was observed ( P >0.05). ELM improved the morphology of fish intestine, as manifested in significant improvement in the length of intestinal villi, thereby increasing the surface area of the intestinal tract ( P <0.05). Compared with the control group, dietary intake of ELM significantly increased the intestinal microbial ACE, Chao1, and Shannon indexes of fish ( P <0.05), indicated that the intestinal microbial composition and the abundance of the dominant flora of fish were improved. The above results suggested that the dietary supplementation of about 9 g/kg ELM can improve the growth performance, enteric antioxidant capacity, and intestinal morphology and microbial composition, therefore improving the intestinal health of spotted sea bass. The research results provide a theoretical basis for the application of ELM in improving the enteric health of spotted sea bass, and providing a potential solution the occurrence of fish intestinal diseases.

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Advances and challenges in interaction between heteroglycans and Bifidobacterium: Utilization strategies, intestinal health and future perspectives - Long-Qing Li; Xu Chen; Jie Zhu; Shuyan Zhang; Si-Qian Chen; Xiaozhen Liu; Lin Li; Jing-Kun Yan (Trends in Food Science & Technology, 2023)

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Insufficient evidence to link human exposure to heavy metals with biomarkers of glioma - Meng-Yi Xie; Guang-Long Huang; Zhi-Ying Lin; Xiang-Fei Sun; Chen-Chou Wu; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Lycopene ameliorates atrazine-induced spatial learning and memory impairments by inhibiting ferroptosis in the hippocampus of mice - Shi-Yong Zhu; Jun-Ze Jiang; Jia Lin; Lin Liu; Jian-Ying Guo; Jin-Long Li (Food and Chemical Toxicology, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Kainic acid induced hyperexcitability in thalamic reticular nucleus that initiates an inflammatory response through the HMGB1/TLR4 pathway - Dongbin Li; Xiaosi Zhang; Ruoshi Liu; Meixin Long; Shanshan Zhou; Jinghan Lin; Liming Zhang (NeuroToxicology, 2023)

2,3′,4,4′,5-Pentachlorobiphenyl induces mitochondria-dependent apoptosis mediated by AhR/Cyp1a1 in mouse germ cells - Qiu-Yue Wang; Lin Zhang; Xiao-Ying Han; Dong-Mei Wang; Ming-Long Ding; Dong Cheng; Qi-Long He; Shu-Zhen Liu (Journal of Hazardous Materials, 2023)

OSA-linear dextrin enhances the compactness of pea protein isolate nanoparticles: Increase of high internal phase emulsions stability - Xiao-Long Li; Wen-Jie Liu; Bao-Cai Xu; Bao Zhang; Wu Wang; Dong-Lin Su (Food Chemistry, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Ferroptosis-related NFE2L2 and NOX4 Genes are Potential Risk Prognostic Biomarkers and Correlated with Immunogenic Features in Glioma - Li Lin; Xiaona Li; Shunda Zhu; Qingshan Long; Yongzhen Hu; Liyang Zhang; Zexin Liu; Bo Li; Xuesong Li (Cell Biochemistry and Biophysics, 2023)
Ferroptosis is a newfound mode of regulated cell death that may have potential to associate with prognostic or diagnostic factors in glioma. In this research, 5 genes related to glioma were screened through the FerrDb database, and we analyzed the combination between genes and glioma of survival and prognosis via TCGA, GEPIA, TIMER, and other databases. Survival curve and prognostic analysis showed that the overexpression of NFE2L2 and NOX4 , respectively, has a remarkable link with a worse prognosis in glioma. Then, the association between the expression of the two genes and tumor-infiltrating immune cells level was explored based on the GSCA, and the immunity of NFE2L2 and NOX4 based on the TISIDB database was also investigated. In glioma, especially GBM, there is a strong association between gene expression and immune infiltration, even in macrophages, nTreg, and Th2 cells, which play immunosuppressive functions in TME. In conclusion, these results indicate that NFE2L2 and NOX4 could be risk prognosis biomarkers in glioma, and they bound up with immune infiltration and tumor immunity in tumorigenesis.

Ambient nitrogen dioxide and cardiovascular diseases in rural regions: a time-series analyses using data from the new rural cooperative medical scheme in Fuyang, East China - Teng-Fei Dong; Zhen-Qiu Zha; Liang Sun; Ling-Li Liu; Xing-Yang Li; Yuan Wang; Xiang-Long Meng; Huai-Biao Li; Hong-Li Wang; Huan-Huan Nie; Lin-Sheng Yang (Environmental Science and Pollution Research, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Tailored acidic deep eutectic solvents: A multifunctional co-catalyst mediating homogeneous catalysis and heterogeneous separation of ethylene methoxycarbonylation - Jianhua Song; Lin Xu; Xiaoping Wang; Chonghao Chen; Weichong Wang; Haoyu Long; Muhammad Asif Nawaz; Dianhua Liu (Fuel, 2023)

Zeolite NaP1 synthesized from municipal solid waste incineration fly ash for photocatalytic degradation of methylene blue - Qian Chen; Yimeng Zhao; Qili Qiu; Ling Long; Xiaobo Liu; Shunda Lin; Xuguang Jiang (Environmental Research, 2023)

Transcriptome and DNA Methylation Responses in the Liver of Yellowfin Seabream Under Starvation Stress - Yi Long Lin; Zong Xian Zhu; Chun Hui Ai; Ying Ying Xiong; Tong De Liu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Modelling the Public Perception of Urban Public Space Lighting Based on SDGSAT-1 Glimmer Imagery: A Case Study in Beijing, China - Zirong Lin; Weili Jiao; Huichan Liu; Tengfei Long; Yongkun Liu; Shengrong Wei; Guojin He; Boris A. Portnov; Tamar Trop; Ming Liu; Xuwen Li; Chunhui Wen (Sustainable Cities and Society, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Glioma is associated with exposure to legacy and alternative per- and polyfluoroalkyl substances - Meng-Yi Xie; Xiang-Fei Sun; Chen-Chou Wu; Guang-Long Huang; Po Wang; Zhi-Ying Lin; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Sustainable preparation of lignocellulosic nanofibrils and cellulose nanopaper from poplar sawdust - Wei Liu; Shuya Zhang; Kun Liu; Hongbin Yang; Qingyi Lin; Ting Xu; Xueping Song; Haishun Du; Long Bai; Shuangquan Yao; Chuanling Si (Journal of Cleaner Production, 2023)

Insights into integration of polyhydroxyalkanoates (PHAs) production into wastewater treatment: Comparison of different electron acceptors on system function and PHA-producer enrichment - Baozhen Liu; Qinxue Wen; Long Huang; Zhiqiang Chen; Xiao Lin; Shaojiao Liu (Chemical Engineering Journal, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

Design of deep-sea chemical data collector for the seafloor observatory network - Bin Lv; Jie Chen; Hai-lin Liu; Chao Liu; Zhao-wen Zhang; Xiao-nan Zhang; Hao Gao; Yu-long Cai (Marine Georesources & Geotechnology, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Experimental study of energy and frequency characteristics of acoustic emissions induced from tensile and shear cracks in tunnel rockburst process - Yan-Bo Zhang; Peng Liang; Xu-Long Yao; Lin Sun; Bao-Zhu Tian; Xiang-Xin Liu (European Journal of Environmental and Civil Engineering, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Quantitative synthetic MRI reveals grey matter abnormalities in children with drug-naïve attention-deficit/hyperactivity disorder - Shu Su; Yingqian Chen; Yan Dai; Liping Lin; Long Qian; Qin Zhou; Mengsha Zou; Hongyu Zhang; Meina Liu; Xianhong Xiang; Zhiyun Yang (Brain Imaging and Behavior, 2022)

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Oceanic vertical mixing of the lower halocline water in the Chukchi Borderland and Mendeleyev Ridge - Long Lin; Hailun He; Yong Cao; Tao Li; Yilin Liu; Mingfeng Wang (Acta Oceanologica Sinica, 2021)

Osteogenic and Angiogenic Potency of VEGF165-Transfected Canine Bone Marrow Mesenchymal Cells Combined with Coral Hydroxyapatite in Vitro - Quanyin Zhang; Jie Zhang; Lin Chen; Yunjian Fan; Jiazhen Long; Shuguang Liu (Tissue Engineering and Regenerative Medicine, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Effects of Polychlorinated Biphenyls on Animal Reproductive Systems and Epigenetic Modifications - Qi-Long He; Lin Zhang; Shu-Zhen Liu (Bulletin of Environmental Contamination and Toxicology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

The Effects of Installation on the Elastic Stiffness Coefficients of Spudcan Foundations - Wen-Long Lin; Zhen Wang; Fei Liu; Jiang-Tao Yi (Journal of Marine Science and Engineering, 2021)
Subjected to pre-load, spudcan foundations, widely utilized to support offshore jack-up rigs, may penetrate in a few diameters into soft clays before mobilizing sufficient resistance from soil. While its stress–strain behavior is known to be affected by the embedment condition and soil backflow, the small-strain calculation with wished-in-place assumption was previously adopted to analyze its elastic stiffness coefficients. This study takes advantage of a recently developed dual-stage Eulerian–Lagrangian (DSEL) technique to re-evaluate the elastic stiffness coefficients of spudcans after realistically modelling the deep, continuous spudcan penetration. A numerical parametric exercise is conducted to investigate the effects of strength non-homogeneity, embedment depths, and the spudcan’s size on the elastic stiffness. On these bases, an expression is provided such that the practicing engineers can conveniently factor the installation effects into the estimation of elastic stiffness coefficients of spudcans.

Screening of binding proteins that interact with two components of the HOG MAPK pathway by the yeast two-hybrid method in Colletotrichum siamense - Xiaomiao Liao; Xiping Long; Qiguang He; Miao Song; Xiao Li; Wenbo Liu; Yu Zhang; Chunhua Lin; Weiguo Miao (European Journal of Plant Pathology, 2021)

Correction to: Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2021)

Cytotoxicity of polyketides and steroids isolated from the sponge-associated fungus Penicillium citrinum SCSIO 41017 - Limbadri Salendra; Xiuping Lin; Weihao Chen; Xiaoyan Pang; Xiaowei Luo; Jieyi Long; Shengrong Liao; Junfeng Wang; Xuefeng Zhou; Yonghong Liu; Bin Yang (Natural Product Research, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

The Application of Decellularized Adipose Tissue Promotes Wound Healing - Zenan Xia; Xiao Guo; Nanze Yu; Ang Zeng; Loubin Si; Fei Long; Wenchao Zhang; Xiaojun Wang; Lin Zhu; Zhifei Liu (Tissue Engineering and Regenerative Medicine, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Effect of dietary isoleucine on skin mucus barrier and epithelial physical barrier functions of hybrid bagrid catfish Pelteobagrus vachelli × Leiocassis longirostris - Long Yin; Ye Zhao; Xiao-Qiu Zhou; Chao Yang; Lin Feng; Yang Liu; Wei-Dan Jiang; Pei Wu; Jian Zhou; Juan Zhao; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Expression Patterns of Inducible Cre Recombinase Driven by Differential Astrocyte-Specific Promoters in Transgenic Mouse Lines - Neng-Yuan Hu; Ya-Ting Chen; Qian Wang; Wei Jie; Yi-Si Liu; Qiang-Long You; Ze-Lin Li; Xiao-Wen Li; Sophie Reibel; Frank W. Pfrieger; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Transcriptome analysis of axillary bud differentiation in a new dual-axillary bud genotype of sugarcane - Dan Chen; Xin Lu; Xiaoyang Wu; Xiongmei Ying; Wenjie Long; Huosheng Su; Hongbo Liu; Xiuqin Lin; Chaohua Xu; Qing Cai (Genetic Resources and Crop Evolution, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Characterizing the spatial distribution of typical natural disaster vulnerability in China from 2010 to 2017 - Qian Wang; Qi-peng Zhang; Yang-yang Liu; Lin-jing Tong; Yan-zhen Zhang; Xiao-yu Li; Jian-long Li (Natural Hazards, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Analysis of the Seismic Effect of Slopes with Different Shapes Under Dynamic Loads - Gui-Lin Wang; Liang Zhang; Zhi-Wen Huang; Bo-Long Liu; Pei-Yong Qiu (Geotechnical and Geological Engineering, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)

Analysis on velocity distribution and displacement along the profile of a slope using both empirical and analytical methods - Tie-lin Chen; Cheng Zhou; En-long Liu; Feng Dai; Jiao Liu (Journal of Mountain Science, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Elevated Serum and Cerebrospinal Fluid Free Fatty Acid Levels Are Associated with Unfavorable Functional Outcome in Subjects with Acute Ischemic Stroke - Xiao-Xia Duan; Guan-Peng Zhang; Xiao-Bin Wang; Hua Yu; Jia-Li Wu; Ke-Zhi Liu; Lin Wang; Xiang Long (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Developmental changes in digestive enzyme activity in American shad, Alosa sapidissima, during early ontogeny - Xiao-Qiang Gao; Zhi-Feng Liu; Chang-Tao Guan; Bin Huang; Ji-Lin Lei; Juan Li; Zheng-Long Guo; Yao-Hui Wang; Lei Hong (Fish Physiology and Biochemistry, 2017)

Delicaflavone induces autophagic cell death in lung cancer via Akt/mTOR/p70S6K signaling pathway - Yuxia Sui; Hong Yao; Shaoguang Li; Long Jin; Peiying Shi; Zhijun Li; Gang Wang; Shilan Lin; Youjia Wu; Yuxiang Li; Liying Huang; Qicai Liu; et al. (Journal of Molecular Medicine, 2017)

Modulation of Nav1.8 by Lysophosphatidic Acid in the Induction of Bone Cancer Pain - Hai-Li Pan; Ben-Long Liu; Wei Lin; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Similarities and differences in combined toxicity of sulfonamides and other antibiotics towards bacteria for environmental risk assessment - Shuxia Fang; Dali Wang; Xiaoxian Zhang; Xi Long; Mengnan Qin; Zhifen Lin; Ying Liu (Environmental Monitoring and Assessment, 2016)

Spatial analysis of gastric cancer morbidity in regions of rapid urbanization: a case study in Xiamen, China - JiLai Liu; XinHu Li; Tao Lin; Long Dai; GuoQin Zhang; ChaoSheng Zhang; Hong Ye; Vee Gibson; QianJun Zhao (Stochastic Environmental Research and Risk Assessment, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Effects of glutamate on growth, antioxidant capacity, and antioxidant-related signaling molecule expression in primary cultures of fish enterocytes - Jun Jiang; Dan Shi; Xiao-Qiu Zhou; Long Yin; Lin Feng; Yang Liu; Wei-Dan Jiang; Ye Zhao (Fish Physiology and Biochemistry, 2015)

Two new macrosporin dimers from the fungus Alternaria sp. XZSBG-1 - Bin Chen; Lan Liu; Xun Zhu; Jun Wang; Yi Long; Si-Ping Jiang; Ai-Guo Xu; Yong-Cheng Lin (Natural Product Research, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Generation by reverse genetics of an effective attenuated Newcastle disease virus vaccine based on a prevalent highly virulent Chinese strain - Meng-Meng Liu; Jin-Long Cheng; Xiao-Hui Yu; Zhuo-Ming Qin; Fu-Lin Tian; Guo-Zhong Zhang (Biotechnology Letters, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Distribution of metals and brominated flame retardants (BFRs) in sediments, soils and plants from an informal e-waste dismantling site, South China - Junxia Wang; Lili Liu; Jinfu Wang; Bishu Pan; Xiaoxu Fu; Gang Zhang; Long Zhang; Kuangfei Lin (Environmental Science and Pollution Research, 2015)

Collection and evaluation of Primula species of western Sichuan in China - Yin Jia; Jing-Long Zhao; Yuan-Zhi Pan; Ying Xu; Ling-Xia Sun; Qing-Lin Liu (Genetic Resources and Crop Evolution, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Axinelline A, a new COX-2 inhibitor from Streptomyces axinellae SCSIO02208 - Wen Ai; Xiu-Ping Lin; Zhengchao Tu; Xin-Peng Tian; Xin Lu; Fredimoses Mangaladoss; Zhi-Long Zhong; Yonghong Liu (Natural Product Research, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

OsLOX2, a rice type I lipoxygenase, confers opposite effects on seed germination and longevity - Jiexue Huang; Maohong Cai; Qizhang Long; Linglong Liu; Qiuyun Lin; Ling Jiang; Saihua Chen; Jianmin Wan (Transgenic Research, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase - Ping-Lin Ong; Tzu-Ting Chuang; Tzu-Fan Wang; Long-Liu Lin (Biologia, 2014)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Polyphyly of the Padus group of Prunus (Rosaceae) and the evolution of biogeographic disjunctions between eastern Asia and eastern North America - Xiao-Lin Liu; Jun Wen; Ze-Long Nie; Gabriel Johnson; Zong-Suo Liang; Zhao-Yang Chang (Journal of Plant Research, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Erratum to: Comparison of FÖrster-Resonance-Energy-Transfer Acceptors for Tryptophan and Tyrosine Residues in Native Proteins as Donors - Yi zhang; Xiaolan Yang; Lin Liu; Xuexia Huang; Jun Pu; Gaobo Long; Ling Zhang; Dong Liu; Bangtian Xu; Juan Liao; Fei Liao (Journal of Fluorescence, 2013)

Comparison of FÖrster-Resonance-Energy-Transfer Acceptors for Tryptophan and Tyrosine Residues in Native Proteins as Donors - Yi zhang; Xiaolan Yang; Lin Liu; Zuexia Huang; Jun Pu; Gaobo Long; Ling Zhang; Dong Liu; Bangtian Xu; Juan Liao; Fei Liao (Journal of Fluorescence, 2013)

Dramatic genotypic difference in, and effect of genetic crossing on, tissue culture-induced mobility of retrotransposon Tos17 in rice - Chunjing Lin; Xiuyun Lin; Lanjuan Hu; Jingjing Yang; Tianqi Zhou; Likun Long; Chunming Xu; Shaochen Xing; Bao Qi; Yingshan Dong; Bao Liu (Plant Cell Reports, 2012)

Ginsenoside Rg1 inhibits autophagy in H9c2 cardiomyocytes exposed to hypoxia/reoxygenation - Zi-Long Zhang; Yan Fan; Mei-Lin Liu (Molecular and Cellular Biochemistry, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Molecular Cloning, Sequence Analysis, and Expression of the Polygalacturonase-inhibiting Protein (PGIP) Gene in Mulberry - Dongqing Hu; Ruiqiang Dai; Yuhua Wang; Yinghua Zhang; Zhaoyue Liu; Rongjun Fang; Weiguo Zhao; Long Li; Qiang Lin; Liu Li (Plant Molecular Biology Reporter, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Variations in thermal physiology and energetics of the tree shrew (Tupaia belangeri) in response to cold acclimation - Lin Zhang; Peng-fei Liu; Wan-long Zhu; Jin-hong Cai; Zheng-kun Wang (Journal of Comparative Physiology B, 2012)

Historical and botanical evidence of distribution, cultivation and utilization of Linum usitatissimum L. (flax) in China - Fei-Hu Liu; Xia Chen; Bo Long; Rui-Yan Shuai; Chun-Lin Long (Vegetation History and Archaeobotany, 2011)

Biophysical studies of an NAD(P)+-dependent aldehyde dehydrogenase from Bacillus licheniformis - Huei-Fen Lo; Jian-Yu Su; Hsiang-Ling Chen; Jui-Chang Chen; Long-Liu Lin (European Biophysics Journal, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

The influence of genetic polymorphisms and interacting drugs on initial response to warfarin in Chinese patients with heart valve replacement - Shi-Long Zhong; Yuan Liu; Xi-Yong Yu; Dan Xu; Hong-Hong Tan; Qiu-Xiong Lin; Min Yang; Hai-Yan Lao; Shu-Guang Lin (European Journal of Clinical Pharmacology, 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

New cyclitol derivative from a sponge Sarcotragus species - Yonghong Liu; Jee H. Jung; Tunhai Xu; Lijuan Long; Xiuping Lin; Hao Yin; Bin Yang; Xue-Feng Zhou; Xianwen Yang (Natural Product Research, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Differential expression of Gnrh2, Gthβ, and Gthr genes in sterile triploids and fertile tetraploids - Yu Long; Min Tao; Shaojun Liu; Huan Zhong; Lin Chen; Suifei Tao; Yun Liu (Cell and Tissue Research, 2009)

Characterization of the complete genome sequence of pike fry rhabdovirus - Hong-Lian Chen; Hong Liu; Zong-Xiao Liu; Jun-Qiang He; Long-Ying Gao; Xiu-Jie Shi; Yu-Lin Jiang (Archives of Virology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

A 70-kDa molecular chaperone, DnaK, from the industrial bacterium Bacillus licheniformis: gene cloning, purification and molecular characterization of the recombinant protein - Wan-Chi Liang; Xuan-Hui Wang; Min-Guan Lin; Long-Liu Lin (Indian Journal of Microbiology, 2009)

The dipeptidyl carboxypeptidase of Escherichia coli novablue: overproduction and molecular characterization of the recombinant enzyme - Hsiang-Ling Chen; Chen-Tien Chang; Long-Liu Lin; Tein-Yu Li; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2009)

Influence of N-Terminal Truncations on the Functional Expression of Bacillus licheniformis γ-Glutamyltranspeptidase in Recombinant Escherichia coli - Long-Liu Lin; Li-Yu Yang; Hui-Yu Hu; Huei-Fen Lo (Current Microbiology, 2008)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Bone regeneration by BMP-2 enhanced adipose stem cells loading on alginate gel - Yunfeng Lin; Wei Tang; Ling Wu; Wei Jing; Xiaoyu Li; Yao Wu; Lei Liu; Jie Long; Weidong Tian (Histochemistry and Cell Biology, 2008)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Identification of glutamate residues important for catalytic activity of Bacillus stearothermophilus leucine aminopeptidase II - Hsin-Ling Yang; Ruey-Shyang Chen; Wenlung Chen; Long-Liu Lin (Antonie van Leeuwenhoek, 2006)

Directed Mutagenesis of the Conserved Asparagine Residues of Bacillus Stearothermophilus Leucine Aminopeptidase II - Ruey-Shyang Chen; Shin-Ling Yang; Yu-Wen Hua; Meng-Chun Chi; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Phylogenetic Analysis and Biochemical Characterization of a Thermostable Dihydropyrimidinase from Alkaliphilic Bacillus sp. TS-23 - Long-Liu Lin; Wen-Hwei Hsu; Wei-Yi Hsu; Shu-Chen Kan; Hui-Yu Hu (Antonie van Leeuwenhoek, 2005)

Adsorption-elution purification of chimeric Bacillus stearothermophilus leucine aminopeptidase II with raw-starch-binding activity - Yu-Wen Hua; Meng-Chun Chi; Huei-Fen Lo; Lih-Ying Kuo; Kuo-Lung Ku; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Generating oxidation-resistant variants of Bacillus kaustophilus leucine aminopeptidase by substitution of the critical methionine residues with leucine - Meng-Chun Chi; Wei-Mou Chou; Chih-Hsien Wang; Wenlung Chen; Wen-Hwei Hsu; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

Mutational analysis of feedback inhibition and catalytic sites of prephenate dehydratase from Corynebacterium glutamicum - Shih-Kuang Hsu; Long-Liu Lin; Hsueh-Hsia Lo; Wen-Hwei Hsu (Archives of Microbiology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Generating oxidation-resistant variants of Bacillus kaustophilus leucine aminopeptidase by substitution of the critical methionine residues with leucine - Meng-Chun Chi; Wei-Mou Chou; Chih-Hsien Wang; Wenlung Chen; Wen-Hwei Hsu; Long-Liu Lin (Antonie van Leeuwenhoek, 2004)

Identification of essential histidine residues in a recombinant ?-amylase of thermophilic and alkaliphilic Bacillus sp. strain TS-23 - Chen-Tien Chang; Huei-Fen Lo; Meng-Chun Chi; Chia-Yu Yao; Wen-Hwei Hsu; Long-Liu Lin (Extremophiles, 2003)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Deletion analysis of the C-terminal region of the α-amylase of Bacillus sp. strain TS-23 - Huei-Fen Lo; Long-Liu Lin; Wen-Ying Chiang; Meng-Chun Chie; Wen-Hwei Hsu; Chen-Tien Chang (Archives of Microbiology, 2002)

The N-Terminal Signal Sequence and the Last 98 Amino Acids Are Not Essential for the Secretion of Bacillus sp. TS-23 α-Amylase in Escherichia coli - Huei-Fen Lo; Long-Liu Lin; Chien-Cheng Li; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2001)

Identification of Essential Cysteine Residues in 3-Deoxy-d-Arabino-Heptulosonate-7-Phosphate Synthase from Corynebacterium glutamicum - Long-Liu Lin; Hui-Fen Liao; Hungchien Roger Chien; Wen-Hwei Hsu (Current Microbiology, 2001)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)

Expression of Pseudomonas amyloderamosa isoamylase gene in Saccharomyces cerevisiae - Pay-Heng Chen; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 1998)